Nak rak phrai - Wīrasak Čhansongsǣng.; Sangkhom Čhirachūsakun. (Krung Thēp : Yipsī Krup, 2012)
On Dr. Bunsong Lekhakun, preeminent conservationist in Thailand; founder and honorary president of Wildlife Fund Thailand and Dr. Charuchinda Naphitaphat, an environmental conservationist and their love for nature.
"Sō̜ng phūyingyai nai lōk singwǣtlō̜m Thai Nō̜phō̜. Bunsong Lēkhakun læ Dō̜rō̜. Čharučhindā Naphītaphat"--Cover.
Includes index.
In Thai.
Keywords: Bunsong Lēkhakun, -- 1907-1992.; Charuchinda Naphitaphat; Conservationists -- Thailand -- Biography; Environmental protection -- Thailand